Universities in the territories of knowledge building in manizales (2011)
Since the middle of the 20th Century, Manizales has been looking for ways to become a knowledgebased city. In this article, different projects that were initiated, and the reasons for their failure, are critically analyzed. This article also proposes to change course and initiate the formation of a Territorial System of Regional Innovation, in accordance with an endogenous, sustainable and synergistic vision.